Study on the adsorption effect and mechanism of biochar from forest surface fuels on heavy metals - Weilong Zhang; Lixuan Wang; Ruijie Zhang; Dongming Ye; Man Zhang; Fengjun Zhao; Guang Yang (Biomass and Bioenergy, 2027)

Biological fire prevention through fungal degradation: Armillaria mellea alters combustibility of surface fuels in typical China Three-North forests - Furui Jian; Lixuan Wang; Dongming Ye; Guang Yang; Fengjun Zhao; Lin Zhang (Biomass and Bioenergy, 2026)

Butyric acid derived from Pantoea ananatis CE26 suppresses postharvest gray mold by inducing membrane disruption and oxidative stress of Botrytis cinerea - Yushan Du; Liwenqian Wang; Jingyuan Zhan; Nongyu Xia; Baoqing Zhu; Guangjin Li; Fengjun Wang (Food Bioscience, 2026)

CO2 bubble-regulated porous architecture of CS@ZIF-8 microspheres for enhanced alcalase immobilization with improved walnut protein hydrolysis - Jiangjuan Yuan; Xueying Liu; Mingyao Li; Feng Jin; Baokai Cui; Jingzhen Chen; Changzhu Li; Fengjun Wang (Carbohydrate Polymers, 2026)

From structural remodeling to cytoprotection: pH-regulated assembly of walnut protein hydrolysate fibril-chlorogenic acid complexes and transcriptomic insights - Chang Li; Jiangjuan Yuan; Junyang Long; Feng Jin; Baokai Cui; Jingzhen Chen; Changzhu Li; Fengjun Wang (Food Bioscience, 2026)

BrNAC046 involved in hydrogen peroxide-induced leaf senescence of postharvest Chinese flowering cabbage - Fengjun Li; Baoxiang Ren; Lilang Li; Xiangjin Kong; Hanzhi Liang; Hai Liu; Ling Wang; Yueming Jiang (Postharvest Biology and Technology, 2026)

Resveratrol-Eu-layered double hydroxide nanocomposite alleviates radiation-induced lung injury through antioxidant and IL-17/NF-κB-associated anti-inflammatory effects - Fangxiao Cao; Junzhe Yang; Xiaoyi Cai; Xin Zuo; Yiming Wang; Li Du; Yuxin Lu; Xiaochen Cheng; Tingting Liu; Shan Ma; Feiyu Zhao; Shanyue Guan; et al. (Chemical Engineering Journal, 2026)

Integrated physiological, transcriptomic and lipidomic analyses reveal the role of trans-2-octenal in the postharvest preservation of fresh walnut kernels - Jiamei Yuan; Yushan Du; Kun Zhang; Heyue Yang; Guangjin Li; Fengjun Wang (Postharvest Biology and Technology, 2026)

Efficacy and possible mechanism of trans-2-octenal in controlling grey mould caused by Botrytis cinerea on harvested fruit - Jiamei Yuan; Jie Yang; Yushan Du; Liwenqian Wang; Fengjun Wang; Guangjin Li (Postharvest Biology and Technology, 2026)

Novel diethylthiosulfinate suppresses postharvest peach brown rot in vitro and vivo by disrupting carbon metabolism and virulence pathways in Monilinia fructicola - Longshen Wang; Hui He; Ming Zhang; Chenxia Liu; Jinglin Zhang; Qiankun Wang; Liqing Zhang; Fengjun Guo; Yuanqing Liu; Huali Lin; Yongjin Qiao; Hongru Liu (International Journal of Food Microbiology, 2026)

Flocoumafen exposure induces skeletal developmental toxicity and neurotoxicity in zebrafish (Danio rerio) - Tianyi Chen; Fengjun Fan; An Cheng; Yumei Xia; Haoze Chen; Jiakai Fang; Yangyu Chen; Tianjia Li; Anli Wang; Binjie Wang; Weixuan Yao; Yuanzhao Wu (Toxicology Letters, 2026)

Development and characterization of a walnut protein hydrolysate-Fe-vitamin C complex: Enhancing iron bioavailability through phytase-assisted modification - Sibao Zhao; Wenzhen Qiu; Yang Sun; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Establishment and characterization of a novel imatinib-resistant dermatofibrosarcoma protuberans cell line, DFSP-DPH1 - Hao Jiang; Kunqian He; Danli Li; Fengjun Zhu; Yuan Ren; Xinying Li; Yuanyuan Wang; Junbo Zhang; Yuangang Lu (Human Cell, 2025)

A WRKY transcriptional factor, BrWRKY70, involves in stem lignification in postharvest Chinese flowering cabbage by regulating lignin synthesis - Fengjun Li; Ling Wang; Meiting Wu; Yulong Chen; Lilang Li; Hai Liu (Postharvest Biology and Technology, 2025)

Low-field NMR-based deep learning for non-destructive quality assessment of frozen model foods - Qiyong Jiang; Meng Liu; Zhaosheng Wang; Rentang Zhang; Yuxiao Wang; Fengjun Guo; Qing Sun; Cuirong Ren (Food Chemistry, 2025)

The role of hydrolysis on the fibrillization of walnut protein: Self-assembly behavior, structural characteristics - Chang Li; Rui Chen; Jiangjuan Yuan; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Synergistic acceleration of proton migration in osmotic microbial fuel cell: hydrophilic nanochannels coupling acid-base pairs created by functionalized metal-organic frameworks in forward osmosis membrane - Enling Tian; Yuan Liu; Cheng Song; Xingzu Wang; Fengjun Yin; Ling Fang; Shun Lu; Yu Lei; Hong Liu (Water Research, 2025)

Walnut glutenin peptide-based-rhamnolipid composite emulsion gels: Preparation, characterization and application as margarine alternatives - Yizhuo Xu; Leiling Huang; Yalei Zhao; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Transglutaminase-enhanced walnut protein isolate gels: Synergistic effects of double modification on gelation and riboflavin encapsulation - Mengxin Wang; Rui Chen; Long Wu; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Genome-wide identification of the C2-domain abscisic acid-related (CAR) protein family in Rosaceae and functional characterization of PbrCAR1 in pear pollen tube growth - Xueying Liu; Yanhong Zhang; Hong Su; Baofeng Zhang; Fengjun Zhao; Hao Zhang; Chao Tang; Peng Wang; Shaoling Zhang; Wenjie Zhou; Juyou Wu (Planta, 2025)

Unveiling interactions between anammox and denitrification from long-term steady-state scale and transient kinetic scale in a granular sludge system - Hao Tan; Fengjun Yin; Jinjin Zheng; Xuehai Yue; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Hong Liu (Bioresource Technology, 2025)

Preparation of emulsions with resveratrol to form functional coatings: Effect on yellowing of frozen limes during storage - Qiyong Jiang; Meng Liu; Zhaosheng Wang; Rentang Zhang; Yuxiao Wang; Fengjun Guo; Qing Sun (Food Hydrocolloids, 2025)

ADB-FUBINACA-induced developmental toxicity, neurotoxicity, and cardiotoxicity in embryonic zebrafish (Danio rerio) - Yuanzhao Wu; Fengjun Fan; Lu Zhou; Yihang Shen; Anli Wang; Yazhou Qin; Jiye Wang; Weixuan Yao (Environmental Research, 2025)

Electrochemical nitrite sensing using mass transfer signal with a catalyst-free small-sized rotating disk electrode for wastewater monitoring - Fengjun Yin; Xiaohui Yang; Shun Lu; Hanlin Zhang; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Zhaoming Chen; Hong Liu (Water Research, 2025)

Modeling electron competition and pH factor interactions improve cognitions of nitrite accumulation during denitrification - Xuehai Yue; Fengjun Yin; Hao Tan; Junxi Liu; Lin Chang; Xiaohui Yang; Sha Wang; Ying Zhao; Haofei Shi; Wei Zhang; Hong Liu (Environmental Research, 2025)

Lysine Demethylase 5B Alleviates Neuroinflammation in Ischemic Stroke by Repressing Steap4 - Qi Yin; Hua Shao; Jingxin Chai; Shanshan Dang; Fengjun Wang (Cell Biochemistry and Biophysics, 2025)

Near-freezing temperature alters ROS metabolism and gene transcription to enhance peach chilling tolerance and aroma quality - Hongru Liu; Hui He; Qiankun Wang; Shaozhen Li; Fengjun Guo; Changfeng Zhang; Ke Wang; Chenxia Liu; Chunfang Wang; Xiao Wang; Bingjie Chen; Yi Zhang; et al. (Food Research International, 2025)

The source-specific health risk and biological effect assessment of PAHs in Mactra veneriformis from the Bohai Sea and Yellow Sea - Zeyuan Li; Ruicheng Qi; Jingjing Miao; Yufen Li; Qiaoqiao Wang; Fengjun Lei; Manni Wu; Yuanjing Chen; Luqing Pan (Environmental Pollution, 2025)

Biochar promotes the dissolution of inorganic inactive phosphorus by mediating the bacterial community during corn stover and cattle manure composting - Linqin Zhao; Ying Li; Bowen Fan; Mengmeng Wang; Ning Sun; Fengjun Yang (Chemosphere, 2025)

A structural equation model for assessing toxic effects of polycyclic aromatic hydrocarbons on scallop Chlamys farreri and the establishment of a novel integrated biomarker index - Zeyuan Li; Ruicheng Qi; Jingjing Miao; Yufen Li; Qiaoqiao Wang; Fengjun Lei; Manni Wu; Yuanjing Chen; Luqing Pan (Marine Environmental Research, 2025)

Identification and Validation of Lipid Metabolism Gene FASN-Associated miRNA in Wilms Tumor - Xiaoqing Wang; Xiao Li; Lin Tan; Fengjun Zhang; Jing Zhang; Xu Zhao; Yongfei Zhang; Guoqiang Du; Wei Liu (Biochemical Genetics, 2025)

Gallic acid reduces pericarp browning of litchi fruit during storage - Chunlan Wang; Shuting Zhang; Dandan Zhang; Fengjun Li; Lihong Xie; Tingrui Dai; Yueming Jiang (Postharvest Biology and Technology, 2025)

Accumulation characteristics and source analysis of microplastics derived traffic of soil in the Tibetan Plateau - Mengjie Liu; Tianjie Shao; Shengmei Han; Weige Nan; Ruiyuan Wang; Fengjun Xiao; Yudan Wang; Zhibao Dong; Yanhua Wang (Journal of Hazardous Materials, 2024)

L-glutamic acid-functionalized graphene oxide with characteristic of anti-stacking towards efficient adsorption-reduction removal of Cr(VI) - Yuxin Wang; Yueqi Chen; Fengjun Shan; Tingting Zhang; Zhenbin Zhang; Meijun Liu (Journal of Environmental Chemical Engineering, 2024)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

Megaripple stripes in the Qaidam Basin, China: Morphology, grain size and sedimentary characteristics - Lijie Wang; Fengjun Xiao; Zhibao Dong; Huirong Ma; Hao Chen (Geomorphology, 2024)

Walnut protein isolate-epigallocatechin gallate nanoparticles: A functional carrier enhanced stability and antioxidant activity of lycopene - Yuzhen Wang; Jiao Lv; Chang Li; Yizhuo Xu; Feng Jin; Fengjun Wang (Food Research International, 2024)

HCMV IE1/IE1mut Therapeutic Vaccine Induces Tumor Regression via Intratumoral Tertiary Lymphoid Structure Formation and Peripheral Immunity Activation in Glioblastoma Multiforme - Xiaoli Yang; Shasha Jiang; Fengjun Liu; Zonghui Li; Wenxuan Liu; Xianjuan Zhang; Fulong Nan; Jun Li; Meng Yu; Yunyang Wang; Bin Wang (Molecular Neurobiology, 2024)
Glioblastoma multiforme (GBM), a highly malignant invasive brain tumor, is associated with poor prognosis and survival and lacks an effective cure. High expression of the human cytomegalovirus (HCMV) immediate early protein 1 (IE1) in GBM tissues is strongly associated with their malignant progression, presenting a novel target for therapeutic strategies. Here, the bioluminescence imaging technology revealed remarkable tumor shrinkage and improved survival rates in a mouse glioma model treated with HCMV IE1/IE1mut vaccine. In addition, immunofluorescence data demonstrated that the treated group exhibited significantly more and larger tertiary lymphoid structures (TLSs) than the untreated group. The presence of TLS was associated with enhanced T cell infiltration, and a large number of proliferating T cells were found in the treated group. Furthermore, the flow cytometry results showed that in the treatment group, cytotoxic T lymphocytes exhibited partial polarization toward effector memory T cells and were activated to play a lethal role in the peripheral immunological organs. Furthermore, a substantial proportion of B cells in the draining lymph nodes expressed CD40 and CD86. Surprisingly, quantitative polymerase chain reaction indicated that a high expression of cytokines, including chemokines in brain tumors and immune tissues, induced the differentiation, development, and chemokine migration of immune cells in the treated group. Our study data demonstrate that IE1 or IE1mut vaccination has a favorable effect in glioma mice models. This study holds substantial implications for identifying new and effective therapeutic targets within GBM.

Fast circulatory nitrification/denitrification process using continuous flow synchronous settling reactors promotes organic utilization efficiency in nitrogen removal - Fengjun Yin; Haotian Wei; Xuehai Yue; Hao Tan; Xiaohui Yang; Shun Lu; Sha Wang; Ying Zhao; Hong Liu (Chemical Engineering Journal, 2024)

Core microbes identification and synthetic microbiota construction for the production of Xiaoqu light-aroma Baijiu - Huan Wang; Yumei Wang; Yulei Ruan; Dan Ma; Han Wang; Shengzhi Yang; Linjie Lyu; Fengjun Yang; Xiaole Wu; Yefu Chen (Food Research International, 2024)

Sedimentary Environment, Tectonic Setting, and Uranium Mineralization Implications of the Yimin Formation, Kelulun Depression, Hailar Basin, China - Fanmin Meng; Fengjun Nie; Fei Xia; Zhaobin Yan; Da Sun; Wenbo Zhou; Xin Zhang; Qing Wang (Journal of Marine Science and Engineering, 2024)
The sandstone-type uranium deposit of the Kelulun Depression is the first industrially valuable uranium deposit discovered in the Hailar Basin. This study performed a systematic examination of 17 sandstone samples from the Yimin Formation in the Kelulun Depression based on various analytical techniques. The findings of the current study were synthesized with previous research to investigate the impact of the redox conditions and the tectonic background of the source area, as well as the paleoclimatic evolution of the Yimin Formation on uranium mineralization. The elemental Mo, U/Th, V/Cr, Ni/Co, and V/(V + Ni) ratios indicate that the paleowater was in an oxygen-rich environment during the deposition of the Yimin Formation. Additionally, the C-value, Sr/Cu, Al2O3/MgO, and Rb/Sr ratios indicate that the Yimin Formation was formed in a paleoclimate characterized by arid-to-semi-arid conditions. The geochemical characteristics of the observed elements indicated that the sediment source of the Yimin Formation was mainly felsic rocks from the upper continental crust, the weathering of the rock was weak, and the tectonic background was a passive continental margin. Coffinite is distributed in the form of cementation and stellates within or around pyrite crystals, and uranium-titanium oxide is mostly distributed in an irregular granular distribution in the biotite cleavage fractures of the study area. In summary, the findings of this study reveal that the tectonic settings, provenance, uranium source, paleoclimate, and oxygen-rich paleowater of the Yimin Formation have important geological significance for the large-scale uranium mineralization of the Kelulun Depression.

Mechanisms underlying the effect of walnut pellicle extracts and its four representative polyphenols on in vitro digestion of walnut protein isolate - Yuzhen Wang; Shinuo Cao; Yuyan Meng; Yifan Cheng; Zeyu Han; Fengjun Wang (Food and Bioproducts Processing, 2024)

Biochar application can enhance phosphorus solubilization by strengthening redox properties of humic reducing microorganisms during composting - Bowen Fan; Changjiang Zhao; Liqin Zhao; Mengmeng Wang; Ning Sun; Zoutong Li; Fengjun Yang (Bioresource Technology, 2024)

Single-Cell RNA Sequencing Transcriptomics Revealed HCMV IE2-Related Microglia Responses in Alzheimer’s-Like Disease in Transgenic Mice - Fengjun Liu; Zhifei Wang; Delei Niu; Xianjuan Zhang; Fulong Nan; Shasha Jiang; Jun Li; Meng Yu; Xiaoli Yang; Shuyun Zhang; Xiaoqiong Zhou; Hui Wang; et al. (Molecular Neurobiology, 2024)
Although multiple factors are known to concur with Alzheimer’s disease (AD), the relationship between human cytomegalovirus (HCMV) and AD-like disease is unclear. Here, we propose a hypothesis that HCMV immediate-early 2 (IE2) protein promotes microglia activation and thus leads to AD-like disease. We successfully constructed IE2 transgenic mice expressing IE2 in the hippocampus. Single-cell sequencing analysis revealed that IE2 promoted the activation of microglia and upregulated the expression of disease-associated microglia genes. Differentially expressed gene analysis and pathway enrichment revealed that IE2 upregulated immune and nervous system disease-related genes. Immunohistochemical analysis showed that the expressions of both amyloid precursor protein (APP) and p-Tau were significantly upregulated in the brains of IE2 mice and were markers of AD. Taken together, these findings provide useful insights into AD-like disease activated by HCMV IE2.

Newcastle disease virus suppresses antigen presentation via inhibiting IL-12 expression in dendritic cells - Fulong Nan; Wenlong Nan; Xin Yan; Hui Wang; Shasha Jiang; Shuyun Zhang; Zhongjie Yu; Xianjuan Zhang; Fengjun Liu; Jun Li; Xiaoqiong Zhou; Delei Niu; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Evaluation of toxicity of heated tobacco products aerosol and cigarette smoke to BEAS-2B cells based on 3D biomimetic chip model - Hongjuan Wang; Fengjun Lu; Yushan Tian; Sen Zhang; Shulei Han; Yaning Fu; Jun Li; Pengxia Feng; Zhihao Shi; Huan Chen; Hongwei Hou (Toxicology in Vitro, 2024)

A comprehensive assessment framework for the risk and source of polycyclic aromatic hydrocarbons (PAHs) using two weight of evidence (WOE) approaches in bays of Shandong Province, China - Zeyuan Li; Ruicheng Qi; Jingjing Miao; Yufen Li; Qiaoqiao Wang; Fengjun Lei; Manni Wu; Yuanjing Chen; Luqing Pan (Journal of Cleaner Production, 2023)

Strong links between aggregate stability, soil carbon stocks and microbial community composition across management practices in a Chinese dryland cropping system - Fengjun Zheng; Xiaotong Liu; Mengni Zhang; Shengping Li; Xiaojun Song; Bisheng Wang; Xueping Wu; Kees Jan van Groenigen (CATENA, 2023)

Rice bran is a key structure affecting high nutrition and low toxicity of indica hybrid rice (Oryza sativa L.) - Yu Fan; Yujie Yuan; Zhiyou Gong; Yajun Wang; Xiufeng Mei; Fengjun Yan; Tao Wang; Fei Deng; Yong Chen; Xiaolong Lei; Jianfeng Hu; Youfeng Tao; et al. (Journal of Cereal Science, 2023)

Exosomal miR-17–92 derived from human mesenchymal stem cells promotes wound healing by enhancing angiogenesis and inhibiting endothelial cell ferroptosis - Wenbo Nie; Xuemiao Huang; Lijing Zhao; Taiwei Wang; Dan Zhang; Tianxin Xu; Lin Du; Yuxiang Li; Weiyuan Zhang; Fengjun Xiao; Lisheng Wang (Tissue and Cell, 2023)

Metagenomic analysis reveals the short-term influences on conjugation of blaNDM-1 and microbiome in hospital wastewater by silver nanoparticles at environmental-related concentration - Haichen Wang; Changhang Min; Fengjun Xia; Yubing Xia; Mengli Tang; Jun Li; Yongmei Hu; Mingxiang Zou (Environmental Research, 2023)

Human Cytomegalovirus IE2 Disrupts Neural Progenitor Development and Induces Microcephaly in Transgenic Mouse - Delei Niu; Xianjuan Zhang; Shuyun Zhang; Tianyu Fan; Xiaoqiong Zhou; Hui Wang; Xueming Zhang; Fulong Nan; Shasha Jiang; Fengjun Liu; Yunyang Wang; Bin Wang (Molecular Neurobiology, 2023)
Human cytomegalovirus (HCMV) is a significant contributor to congenital birth defects. Limited by the lack of animal models, the pathogenesis of neurological damage in vivo caused by HCMV infection and the role of individual viral genes remain to be elucidated. Immediate early (IE2) protein may play a function in neurodevelopmental problems caused by HCMV infection. Here, this study intended to investigate IE2’s long-term effects on development of the brain in IE2-expressing transgenic mice (Rosa26-LSL-IE2 +/− , Camk2α-Cre) aimed to observe the phenotype of postnatal mice. The expression of IE2 in transgenic mice was confirmed by PCR and Western blot technology. We collected mouse brain tissue at 2, 4, 6, 8, and 10 days postpartum to analyze the developmental process of neural stem cells by immunofluorescence. We discovered that transgenic mice (Rosa26-LSL-IE2 +/− , Camk2α-Cre) can reliably produce IE2 in the brain at various postpartum phases. Furthermore, we also observed the symptoms of microcephaly in postnatal transgenic mice, and IE2 can damage the amount of neural stem cells, prevent them from proliferating and differentiating, and activate microglia and astrocytes, creating an unbalanced environment in the brain’s neurons. In conclusion, we demonstrate that long-term expression of HCMV-IE2 can cause microcephaly through molecular mechanisms affecting the differentiation and development of neural stem cells in vivo. This work establishes a theoretical and experimental foundation for elucidating the molecular mechanism of fetal microcephaly brought by HCMV infection in throughout the period of neural development of pregnancy. Graphical Abstract

Ceramsite made from remediated soil: A risk assessment of its potential role serving as urban street cushion - Chi Zhang; Genfu Wang; Fengjun Xu; Zhenghua Wu; Chaofeng Shen; Chao Wu; Zhong Zhong; Jianmeng Chen (Bulletin of Environmental Contamination and Toxicology, 2023)

Seasonal differences in the spatial patterns of wildfire drivers and susceptibility in the southwest mountains of China - Wenquan Wang; Fengjun Zhao; Yanxia Wang; Xiaoyuan Huang; Jiangxia Ye (Science of The Total Environment, 2023)

Promotion and inhibition effects of wax on methane hydrate formation and dissociation in water-in-oil emulsions - Shikun Tong; Pengfei Li; Fengjun Lv; Zhiyuan Wang; Weiqi Fu; Jianbo Zhang; Litao Chen; Xuerui Wang (Fuel, 2023)

A NAC transcriptional factor BrNAC029 is involved in cytokinin-delayed leaf senescence in postharvest Chinese flowering cabbage - Fengjun Li; Youxia Shan; Haobin Wang; Guoxiang Jiang; Xiaochun Ding; Hanzhi Liang; Chunlan Wang; Xiangjin Kong; Lihong Xie; Yueming Jiang (Food Chemistry, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Facilitating proton transport by endowing forward osmosis membrane with proton conductive sites in osmotic microbial fuel cell - Enling Tian; Yuan Liu; Fengjun Yin; Shun Lu; Lei Zheng; Xingzu Wang; Zongping Wang; Hong Liu (Chemical Engineering Journal, 2023)

Role of Penicillin-Binding Protein 1b in the Biofilm Inhibitory Efficacy of Ceftazidime Against Escherichia coli - Fengjun Sun; Yixuan Sun; Yu Wang; Qian Yuan; Lirong Xiong; Wei Feng; Peiyuan Xia (Current Microbiology, 2022)

Differences in Rice Productivity and Growth Attributes Under Different Paddy-Upland Cropping Systems - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Wanjun Ren (International Journal of Plant Production, 2022)

Mesozoic intracontinental deformation of the Alxa Block in the middle part of Central Asian Orogenic Belt: A review - Jin Zhang; Yannan Wang; Junfeng Qu; Beihang Zhang; Heng Zhao; Long Yun; Tianyi Li; Pengfei Niu; Fengjun Nie; Jie Hui; Yiping Zhang (International Geology Review, 2021)

Incineration experiment of medical waste of novel coronavirus pneumonia (COVID-19) in a mobile animal carcass incinerator - Shaorui Zhang; Yanjun Zhang; Fengjun Wang; Da Kang; Jingjie Wang; Minghao Wang; Chunwei Zhang; Yongtang Wang; Hong Liu; Baodong Zhou; Yong Wu (Waste Disposal & Sustainable Energy, 2021)

Dental Pulp Stem Cell-Derived Extracellular Vesicles Mitigate Haematopoietic Damage after Radiation - Fanxuan Kong; Chu-Tse Wu; Panpan Geng; Chao Liu; Fengjun Xiao; Li-Sheng Wang; Hua Wang (Stem Cell Reviews and Reports, 2021)
Radiation therapy can cause haematopoietic damage, and mesenchymal stem cells (MSCs) derived extracellular vesicles (EVs) have been shown to reverse this damage. Our previous research showed that dental pulp stem cells (DPSCs) have a strong proliferation capacity and can produce abundant amounts of EVs to meet the requirements for use in vitro and in vivo. DPSCs derived EVs (DPSCs-EVs) are evaluated for their effect on reducing haematopoietic damage. Haematopoietic stem cell (HSC) numbers and function were assessed by flow cytometry, peripheral blood cell counts, histology and bone marrow transplantation. Epidermal growth factor (EGF) was used as a reference for evaluating the efficiency of EVs. miRNA microarray was employed to find out the changes of miRNA expression after cells being irradiated in vivo and the role they may play in mitigation the radiation caused injury. We observed the effect of DPSCs-EVs on promoting proliferation and inhibiting apoptosis of human umbilical vein endothelial cells (HUVECs) and FDC-P1 cells in vitro. We found that DPSCs-EVs and EGF could comparably inhibit the decrease in WBC, CFU count and KSL cells in vivo. We also verified that EVs could accelerate the recovery of long-term HSCs. In summary, DPSCs-EVs showed an apoptosis resistant effect on HUVECs and FDC-P1 cells after radiation injury in vitro. EVs from DPSCs were comparable to EGF in their ability to regulate haematopoietic regeneration after radiation injury in vivo. Radiation could alter the expression of some miRNAs in bone marrow cells, and EVs could correct these changes to some extent.

The impact of energy-intensive industries on air quality in China’s industrial agglomerations - Xiaoping Zhang; Meihan Lin; Zhenbo Wang; Fengjun Jin (Journal of Geographical Sciences, 2021)

Residual nitrogen from preceding garlic crops is important for double-cropped rice - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Nkrumah Malik; Wanjun Ren (Nutrient Cycling in Agroecosystems, 2020)

Characteristics of vertical karst development and grouting reinforcement engineering practice of the Ordovician top in the Feicheng coalfield, China - Mei Qiu; Fengjun Huang; Jingxue Wang; Longqing Shi; Xingyue Qu; Tianhao Liu (Carbonates and Evaporites, 2020)

Tectonic evolution of the western Ordos Basin during the Palaeozoic-Mesozoic time as constrained by detrital zircon ages - Beihang Zhang; Jin Zhang; Heng Zhao; Fengjun Nie; Yannan Wang; Yiping Zhang (International Geology Review, 2019)

Complete mitochondrial genome of the Himalayan Monal Lophophorus impejanus (Phasianidae), with phylogenetic implication - Yang Chen; Fengjun Li; Qi Zhang; Qiong Wang (Conservation Genetics Resources, 2018)

Effects of wheat straw mulch application and nitrogen management on rice root growth, dry matter accumulation and rice quality in soils of different fertility - Fengjun Yan; Yongjian Sun; Hui Xu; Yaozhu Yin; Haiyue Wang; Chunyu Wang; Changchun Guo; Zhiyuan Yang; Yuanyuan Sun; Jun Ma (Paddy and Water Environment, 2018)

Complete mitochondrial genome of the Burmese Short-Tailed Shrew, Blarinella wardi (Mammalia, Soricidae) - Fengjun Li; Xuming Wang; Qi Zhang; Haijun Jiang; Haixue Wei; Qing Wang; Shunde Chen; Shaoying Liu (Conservation Genetics Resources, 2018)

The complete mitochondrial genome of Chinese Shrew, Sorex sinalis (Soricidae) - Xuming Wang; Fengjun Li; Qi Zhang; Haijun Jiang; Shunde Chen; Shaoying Liu (Conservation Genetics Resources, 2018)

A monocentric centerline extraction method for ring-like blood vessels - Fengjun Zhao; Feifei Sun; Yuqing Hou; Yanrong Chen; Dongmei Chen; Xin Cao; Huangjian Yi; Bin Wang; Xiaowei He; Jimin Liang (Medical & Biological Engineering & Computing, 2018)

Spatial evolution of coal transportation at coastal ports in China - Wei Wang; Chengjin Wang; Fengjun Jin (Journal of Geographical Sciences, 2018)

Development of a multiplex fluorescence quantitative PCR for detection of genetically modified organisms - Fengjun Wang; Junli Feng; Sudan Ye; Hannian Huang; Xianglin Zhang (Biologia, 2018)

Late Palaeozoic tectonic setting of the southern Alxa Block, NW China: constrained by age and composition of diabase - Yiping Zhang; Jin Zhang; Xuanhua Chen; Yannan Wang; Heng Zhao; Fengjun Nie; Beihang Zhang (International Geology Review, 2017)

Understanding relationship between accessibility and economic growth: a case study from China (1990–2010) - Jingjuan Jiao; Jiaoe Wang; Fengjun Jin; Chao Du (Chinese Geographical Science, 2016)

A highly robust and optimized sequence-based approach for genetic polymorphism discovery and genotyping in large plant populations - Ning Jiang; Fengjun Zhang; Jinhua Wu; Yue Chen; Xiaohua Hu; Ou Fang; Lindsey J. Leach; Di Wang; Zewei Luo (Theoretical and Applied Genetics, 2016)

Progress of research on transportation geography in China - Fengjun Jin; Chengjin Wang; Youhui Cao; Xiaoshu Cao; Jiaoe Wang; Teqi Dai; Jingjuan Jiao (Journal of Geographical Sciences, 2016)

Molecular characterization and expression analyses of ST8Sia II and IV in piglets during postnatal development: lack of correlation between transcription and posttranslational levels - Xi Zhu; Yue Chen; Nai Zhang; Zhiqiang Zheng; Fengjun Zhao; Ni Liu; Chunlong Lv; Frederic A. Troy; Bing Wang (Glycoconjugate Journal, 2015)

Evolution of regional transport dominance in China 1910–2012 - Hao Hu; Jiaoe Wang; Fengjun Jin; Nan Ding (Journal of Geographical Sciences, 2015)

Significant progress in transport geography in China - Chengjin Wang; Fengjun Jin (Journal of Geographical Sciences, 2015)

Transportation development transition in China - Fengjun Jin; Jinxue Ding; Jiao’e Wang; Dong Liu; Chengjin Wang (Chinese Geographical Science, 2012)

China’s regional transport dominance: Density, proximity, and accessibility - Fengjun Jin; Chengjin Wang; Xiuwei Li; Jiao’e Wang (Journal of Geographical Sciences, 2010)